Cosmic ray solar modulation and Forbush decrease analyses based on atmospheric neutron spectrometry at mountain altitude and GEANT4 simulations of extensive air showers. Issue 12 (3rd December 2013) - Cheminet, A.; Hubert, G.; Lacoste, V.; Maurin, D.; Derome, L.
Abstract [1] A Bonner sphere spectrometer extended to high energies (HERMEIS) was set up at the summit of the Pic du Midi de Bigorre in the French Pyrenees (altitude: +2, 885 m; geomagnetic cutoff: 5.6 GV) in May 2011. The spectral fluence rate distribution of the cosmic ray induced neutrons was continuously measured over a broad energy range from meV up to several GeV and with a 1 h time resolution. While the Sun's activity was increasing and reaching its 24th maximum in the 11 year solar cycle, some Forbush decreases were observed in the atmospheric secondary radiation at mountain altitude. We investigated the evolution of the cascade fluence rate (i.e., neutrons with energy greater than 20 MeV) during the March 2012 events with a series of strong coronal mass ejections hitting the Earth's magnetosphere. The amplitude of the greatest Forbush decrease peaked at 10%. Then, a simulation work based on the GEANT4 toolkit was carried out to quantify the solar modulation induced on the galactic cosmic ray transportation during these events. We performed calculations of extensive air showers generated by monoenergetic primaries (Hydrogen and Helium nuclei) for several zenith incidences. Hence, a complete database was built and validated. We derived an analytical model to estimate the atmospheric neutron spectrum at the Pic du Midi according to primary spectra which only depend on the solar modulation potential (force field approximation). We compared the solar modulation potentials obtained in March 2012 with the ones derived by the neutron monitor yield method. Finally, a satisfying agreement was found.